Beyond postcolonialism :dreams and realities of a nation - Jasbir Jain (Rawat, 2019)
"Beyond Postcolonialism: Dreams and Realities of a Nation questions the narrow framework that postcolonial provides and seeks to free resistance literature from being confined within it. Taking up the fiction of the last half century, the work considers the dreams and realities that have engaged the attention of the writers from 1947 to the present across languages and regions focusing on the concerns of gender, caste, religion, nation-building and aesthetics both at home and in diasporic writing. The historical novel has leapt out of its earlier limits to take up a counter position to contemporary events. It is no longer a mere recording or an exoticism of the past; instead, it is an interrogation, a self-introspection and a face-to-face confrontation with the past that lays bare both the pain of suffering and the consciousness of the guilt of the nation.Dalit writing has also thrown up a challenge to classical aesthetics with its raw, experience-based narratives. A new realism has come into being - a realism that exposes the roots rather than the mere surface, and stretches the limits of existing modes. Working through these tropes of guilt and self-analysis, reworking the relationship between the individual and community, the Indian novel today projects the need for an active intellectualism rooted in social concerns - a need based on emotional logic - and a constant questioning of one`s relationship to the larger totality."